Impact of specialized physical training programs on physical fitness in athletes - Siramaneerat, I.; Chaowilai, C. (Journal of Human Sport & Exercise, 2022)
Introduction. Physical fitness is important to athletes because it allows for the highest ability of the athletes participating in any competition. Speed, agility, and quickness training (SAQ) is a form of training that is widely used to help athletes develop themselves in those areas. In addition, training programs can help athletes succeed by developing neuromuscular systems, improve the efficiency of movement, and in general increase their abilities. Objective. This research aims to compare the effect of the SAQ training program on physical fitness in athletes. Athletes are students of Rajamangala University of Technology Thanyaburi, 1st-4th year, aged over 18 years, consisting of 30 people, divided into 1 control group and 1 experimental group. The tools used in this research are a physical fitness test, and the SAQ training program. The frequency, percentage, average, standard deviation and t-test for dependent sample at the statistical significance level of .05. Results. The study found that in the experimental group, the mean values of hand force (t = 2.124, p-value = .05), counter movement jump (t = 2.307, p-value = .029) , sitting, bent forward (t = 2.87, p-value = .008) were significantly higher than the control group at the statistical significance of .05. The experimental group had lower storage and running mean values (t = -14.760, p-value = .000) than the control group with statistical significance of .05. Conclusion. Applicable to athletes in training or anyone interested in using the SAQ training program in order to increase physical fitness in athletes. Moreover, trainers can apply the SAQ training program to other sports such as tennis, football, etc.